Immunohistochemical localization of epithelial membrane antigen, carcinoembryonic antigen and secretory component in urinary bladder cancer - Takashi, M (Hinyokika kiyo. Acta urologica Japonica, 1986)
To clarify the relationship between the immunohistochemical distribution pattern of epithelial antigens in transitional cell carcinomas and their histopathological grading and staging, epithelial membrane antigen (EMA), carcinoembryonic antigen (CEA) and secretory component (SC) were localized. Formalin-fixed paraffin-embedded sections from 55 patients with bladder carcinoma were stained by the indirect immunoperoxidase method. In normal transitional epithelium, EMA was found on the luminal side of the plasma membrane of a few surface layers, and in the cytoplasm of the superficial cells. In the lower grade and stage of transitional cell carcinoma, only the luminal surface of superficial cells was positively stained. Membrane and cytoplasmic staining of EMA was frequently found in the intermediate and basal layers of the carcinoma, and the incidence of cytoplasmic staining increased with the higher grade and stage. CEA was not detected in normal epithelium. Cytoplasmic staining of CEA was progressively more frequent in the higher grade and stage of transitional cell carcinoma. In normal epithelium SC was observed on the apical surface plasma membrane and in the cytoplasm of the superficial cells, as shown in the immunohistochemical staining for EMA. The correlation of immunohistochemical detection of SC with the grade or stage was not as good as the correlations for EMA or CEA. These findings suggest that immunohistochemical examination for EMA, CEA and SC in bladder carcinoma could provide valuable information for grading or staging in pathological diagnosis